An integrated weed management strategy for the control of horseweed (Conyza canadensis). Issue 1 (14th January 2021) - Vanhie, Theodore R.; Tardif, François J.; Smith, Peter; Vazan, Saeed; Cowbrough, Michael; Swanton, Clarence J.
Abstract: Multiple herbicide-resistant populations of horseweed [ Conyza canadensis (L.) Cronquist] continue to spread rapidly throughout Ontario, notably in areas where no-till soybean [Glycine max (L.) Merr.] is grown. The occurrence of multiple herbicide resistance within these populations suggests that the future role of herbicide tank mixtures as a means of control will be limited. An integrated weed management strategy utilizing complementary selection pressures is needed to reduce the selection intensity of relying solely on herbicides for control. Field studies were conducted in 2018 and 2019 to test the hypothesis: if fall-seeded cereal rye ( Secale cereale L.) can reduce C. canadensis seedling density and suppress seedling growth, then the interaction(s) of complementary selection pressures of tillage, cereal rye, and herbicides would improve the level of C. canadensis control. Laboratory studies were conducted to determine whether the allelopathic compound 2-benzoxazolinone (BOA) affected the root development of C. canadensis seedlings. The interactions observed among multiple selection pressures of tillage, cereal rye, and herbicides were inconsistent between the 2 yr of study. A monoculture of cereal rye seeded in the fall, however, did reduce seedling height and biomass of C. canadensis consistently, but not density. This reduction in seedling height and biomass was likely caused by the allelopathic compound BOA, which reduced seedling root development. Control of C. canadensis seedlings in the spring required the higher registered rates of dicamba or saflufenacil. The addition of shallow fall tillage and the presence of cereal rye did not improve the variability in control observed notably with 2, 4-D or the lower rates of saflufenacil or dicamba. With the implementation of complementary weed management strategies, environmental variables in any given year will likely have a direct influence on whether these interactions are additive or synergistic.